2016
DOI: 10.18632/oncotarget.12385
|View full text |Cite
|
Sign up to set email alerts
|

miR128-1 inhibits the growth of glioblastoma multiforme and glioma stem-like cells via targeting BMI1 and E2F3

Abstract: MicroRNA128-1 (miR128-1), as a brain-specific miRNA, is downregulated in glioblastoma multiforme (GBM) and closely associated with the progression of GBM. However, the underlying molecular mechanism of the downregulation and its role in the regulation of tumorigenesis and anticancer drug resistance in GBM remains largely unknown. In the current study,we found that miR128-1 was downregulated in GBM and glioma stem-like cells (GSCs). Intriguingly, treatment with the DNA methylation inhibitors 5-Aza-CdR (Aza) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
48
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(49 citation statements)
references
References 35 publications
1
48
0
Order By: Relevance
“…RT-PCR was performed on a 7500 real-time-PCR System (Applied Biosystems, Carlsbad, CA, USA) using Taqman probes for miR-29a (Applied Biosystems, 4427975) and primers for Bmi1. The sequence of the primers: Primer sets (5'-3') were as follows: Bmi1: CACCAGAGAGATGGACTGACAA and AGGAAACTGTGGATGAGGAGAC [21]. The 2 -ΔΔCt method was used to calculate expression levels.…”
Section: Quantitative Real-time Pcr (Qrt-pcr)mentioning
confidence: 99%
“…RT-PCR was performed on a 7500 real-time-PCR System (Applied Biosystems, Carlsbad, CA, USA) using Taqman probes for miR-29a (Applied Biosystems, 4427975) and primers for Bmi1. The sequence of the primers: Primer sets (5'-3') were as follows: Bmi1: CACCAGAGAGATGGACTGACAA and AGGAAACTGTGGATGAGGAGAC [21]. The 2 -ΔΔCt method was used to calculate expression levels.…”
Section: Quantitative Real-time Pcr (Qrt-pcr)mentioning
confidence: 99%
“…miR‐128 was reported as oncogene or tumour suppressor in various cancers. For example, miR‐128 was reported to be downregulated in cancer tissues and represses growth and metastasis of bladder cancer, lung cancer, and glioblastoma multiforme . However, different studies of the miR‐128 in carcinoma reported discordant conclusions.…”
Section: Discussionmentioning
confidence: 99%
“…miR-128-1 is supposed to act as a tumor suppressor inhibiting tumor cell proliferation, invasion and self-renewal by direct targeting of bMI1 and E2F3 in glioblastomas (67). Furthermore, it has been associated with inhibition of the mTOR signaling pathway in glioblastomas.…”
Section: Discussionmentioning
confidence: 99%